Etiologies and long-term outcome of pediatric hemophagocytic lymphohistiocytosis and macrophage activation syndrome in Taiwan: a single-center retrospective study - Wang, Ching-Yu; Lee, Jyh-Hong; Lee, Ni-Chung; Hu, Ya-Chiao; Chang, Hsiu-Hao; Wang, Li-Chieh; Lin, Yu-Tsan; Yang, Yao-Hsu; Chiang, Bor-Luen; Yu, Hsin-Hui (Frontiers in Immunology, 2025)
Hemophagocytic lymphohistiocytosis (HLH) and macrophage activation syndrome (MAS) are life-threatening hyperinflammatory conditions. Primary HLH is caused by genetic mutations associated with defective cytotoxicity, while secondary HLH is triggered by various factors, including infection-associated HLH (IAHS), rheumatic diseases-associated HLH (MAS), or malignancy-associated HLH (M-HLH). We retrospectively reviewed the medical records of patients younger than 20 years of age with physician-diagnosed HLH or MAS between January 2005 and July 2022 in a large medical center in Taiwan. Seven patients were prospectively enrolled since Jan 2019. Clinical and laboratory features, treatments rendered, and outcomes of patients with HLH/MAS were analyzed. Fifty-two patients with HLH/MAS were included in this study and classified as follows: 21 (40.4%) with IAHS, 20 (38.5%) with MAS, 5 (9.6%) with M-HLH, 4 (7.7%) with primary HLH, and 2 (3.8%) with unclassified HLH (U-HLH). The median age of diagnosis for all patients was 9.04 years, while it ranged between 5.12 (for primary HLH) to 16.03 (for M-HLH) years. Two-year probabilities of survival of each group of HLH/MAS were 100%, 85.7%, 65.63%, 25%, and 20% for patients with U-HLH, IAHS, MAS, primary HLH, and M-HLH, respectively (log-rank, P =0.0018). The five-year probability of survival was 65.63% for patients with MAS. M-HLH and ICU admission were significantly associated with mortality. Infections and rheumatic diseases are the main triggers or conditions associated with pediatric HLH/MAS, whereas malignancy is an important etiology among adolescents.